Targeting ERK induced cell death and p53/ROS-dependent protective autophagy in colorectal cancer - Wunan Mi (Nature Publishing Group, 2021)
Abstract In recent years, many studies have shown that autophagy plays a vital role in the resistance of tumor chemotherapy. However, the interaction between autophagy and cell death has not yet been clarified. In this study, a new specific ERK inhibitor CC90003 was found to suppress colorectal cancer growth by inducing cell death both in vitro and in vivo. Studies have confirmed that higher concentrations of ROS leads to autophagy or cell death. In this research, the role of CC90003-induced ROS was verified. But after inhibiting ROS by two kinds of ROS inhibitors NAC and SFN, the autophagy induced by CC90003 decreased, while cell death strengthened. In parallel, protective autophagy was also induced, while in a p53-dependent manner. After silencing p53 or using the p53 inhibitor PFTα, the autophagy induced by CC90003 was weakened and the rate of cell death increases. Therefore, we confirmed that CC90003 could induce autophagy by activating ROS/p53. Furthermore, in the xenograft mouse model, the effect was obtained remarkably in the combinational treatment group of CC90003 plus CQ, comparing with that of the single treatment groups. In a word, our results demonstrated that targeting ERK leads to cell death and p53/ROS-dependent protective autophagy simultaneously in colorectal cancer, which offers new potential targets for clinical therapy.